2014
DOI: 10.1159/000368714
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Enteral Supplementation Enriched with Glutamine, Fiber, and Oligosaccharide on Mucosal Injury following Hematopoietic Stem Cell Transplantation

Abstract: The combination of glutamine, fiber and oligosaccharides (GFO) is thought to be beneficial for alleviating gastrointestinal mucosal damage caused by chemotherapy. A commercial enteral supplementation product (GFO) enriched with these 3 components is available in Japan. We performed a retrospective study to test whether oral GFO decreased the severity of mucosal injury following hematopoietic stem cell transplantation (HSCT). Of 44 HSCT patients, 22 received GFO and 22 did not. Severity of diarrhea/mucositis, o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
74
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(77 citation statements)
references
References 15 publications
2
74
0
1
Order By: Relevance
“…In other patient groups, fibre-containing EN has a positive effect on SCFA production compared with a fibre-free formula (Schneider et al, 2006). Fibre supplementation (plus glutamine and probiotics) may reduce mortality in patients undergoing HPCT (Iyama et al, 2014). This is the first study to report a difference in the microbiota based on level of oral intake post-HPCT and while luminal SCFA levels were not measured, the group who tolerated greater oral intake had higher microbial diversity and SCFA-producing taxa, likely due to greater fibre consumption.…”
Section: Discussionmentioning
confidence: 99%
“…In other patient groups, fibre-containing EN has a positive effect on SCFA production compared with a fibre-free formula (Schneider et al, 2006). Fibre supplementation (plus glutamine and probiotics) may reduce mortality in patients undergoing HPCT (Iyama et al, 2014). This is the first study to report a difference in the microbiota based on level of oral intake post-HPCT and while luminal SCFA levels were not measured, the group who tolerated greater oral intake had higher microbial diversity and SCFA-producing taxa, likely due to greater fibre consumption.…”
Section: Discussionmentioning
confidence: 99%
“…Other dietary components, especially those derived from the family Brassicaceae, are metabolized by the gut microbiota to indole-containing moieties and have protective effects on the intestinal mucosa. A study demonstrated reduced Enterococcus translocation and reduced mortality in HSCT patients who were administered fiber, glutamine, and oligosaccharides [35]. A clinical study investigating the effect of resistant starch as prebiotic to induce buty­rate production by the microbiota for the prevention of acute GvHD is ongoing (www.clinicaltrials.gov: NCT02763033).…”
Section: Modulators Of the Gut Microbiotamentioning
confidence: 99%
“…Iyama et al concluded that GFO supplementation was an effective supportive therapy to decrease the severity of mucosal injury in HSCT. 38 In the systematic review by Van Zyl, 20 significant associations (RR 0.14, p = 0.05) were reported in two studies with adult patients (n = 45) in which fewer grade 3 or 4 mucositis cases were present when patients received IV-GLN vs placebo. Significant results for interventions >14 days (RR 0.19, p = 0.0003) were also obtained in four studies (n = 410) in which presence of grade 3 or 4 mucositis was significantly less in the IV-GLN group after 14 days of consecutive administration.…”
Section: 12mentioning
confidence: 98%
“…23 A possible trend in the objective reduction of mucositis by glutamine supplementation in non-BMT patients receiving chemotherapy and/or radiotherapy has been reported. 37 Furthermore, a Japanese study 38 using a combination of GLN, fibre and oligosaccharides (GFO) was the first retrospective comparative clinical study of mucosal injury in allogeneic HSCT using GFO. Iyama et al concluded that GFO supplementation was an effective supportive therapy to decrease the severity of mucosal injury in HSCT.…”
Section: 12mentioning
confidence: 99%